2019
DOI: 10.1039/c9cc04191e
|View full text |Cite
|
Sign up to set email alerts
|

An earth-abundant system for light-driven CO2 reduction to CO using a pyridinophane iron catalyst

Abstract: A visible-light-driven earth-abundant photocatalytic system for CO2 reduction using an iron catalyst and a copper photosensitizer produces CO as a main product (TONCO = 565) with a high selectivity over H2 production (SelCO2 = 84%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 26 publications
0
29
1
Order By: Relevance
“…Ishitani et al have shown that dimeric Cu complexes with heteroleptic diimine and phosphine ligands are effective photosensitizers to exhibit 273 turnovers of CO in 12 h 37 . The systems employed various copper diimine diphosphine complexes as the photosensitizers, Fe 37 39 , Co 40 , Ni 41 , or Mn 42 , 43 metal complexes as the catalysts, and 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole (BIH) as the sacrificial electron donor that produced CO up to 2680 turnovers under optimal conditions 40 . While Cu diimine photosensitizers exhibit relatively higher activities in photocatalytic CO 2 reduction than organic PS, they require much higher energetic light irradiation owing to their absorption spectra centered at the UV region 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Ishitani et al have shown that dimeric Cu complexes with heteroleptic diimine and phosphine ligands are effective photosensitizers to exhibit 273 turnovers of CO in 12 h 37 . The systems employed various copper diimine diphosphine complexes as the photosensitizers, Fe 37 39 , Co 40 , Ni 41 , or Mn 42 , 43 metal complexes as the catalysts, and 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole (BIH) as the sacrificial electron donor that produced CO up to 2680 turnovers under optimal conditions 40 . While Cu diimine photosensitizers exhibit relatively higher activities in photocatalytic CO 2 reduction than organic PS, they require much higher energetic light irradiation owing to their absorption spectra centered at the UV region 36 .…”
Section: Introductionmentioning
confidence: 99%
“…[Cu(NN) 2 ] + complexes are easier easy to prepare and more stable in the long term than [Cu(PP)(NN)] + ones. 24,25 Finally, the excited state of PS Cu is sufficiently long-lived 26 to ensure reactivity with donor D.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the few trans bond angles that is off 180 • for ZnN 4 Cl 2 complexes [51][52][53] (see the following references with examples of 180 • Cl-Zn-Cl bond angles: [54,55]). Notably, 29 out of 40 of the ZnN 4 Cl 2 complexes in the CSD database [56] actually have a cis arrangement of the chlorides (see [57,58]). All of the bond distances and bond angles in the crystal structure are comparable with similar distances in other structurally characterized six-coordinate zinc(II) complex-containing terminal chlorides [59,60].…”
Section: Description Of Crystal Structuresmentioning
confidence: 99%